The accuracy of ultra-sonographic findings in detection of abdominal tumor size in children (our experience in Children Medical Center) - Ashjaee, Bahar; Azary, Saeedeh; Khalifeh-Soltani, Amin (Iranian Journal of Pediatric Surgery, 2018)
Introduction: Since abdominal tumors are one of the common causes of childhood death, studying the clinico-pathologic features of them is important for early diagnosis. Our aim in this study was to determine these features in Iranian children and to evaluate the accuracy of ultrasonography in diagnosing abdominal masses in children. Materials and Methods: In this retrospective case series study, data about sex, age, primary chief complaint, physical examination, imaging report and pathology finding of 156 children with abdominal tumor, who were admitted to the Children Medical Center in the last 6 years were gathered. Results: Male to female ratio was 0.69. The most common type of tumor in this study was Willm’s (37.5%) and Neuroblastoma (35.7%). Mean age of children with Willm’s tumor and Neuroblastoma was 38.95 and 26.65 months respectively. Ultrasonography has a lower accuracy in patients with tenderness, children with Willm’s tumor, female patients and children under 5 years old. Conclusion: Our different findings regarding tumor type and distribution as opposed to previous studies may be due to genetic and geographic variations. In addition, this study shows that the accuracy of Ultrasonography in children with abdominal tumors depends on children’s sex, age, pain and the type of tumor.